Defining a trade strategy for southern Mediterranean countries - Bouët, Antoine (International Food Policy Research Institute, 2006)
The objective of this paper is to analyze the best trade approach for Southern Mediterranean countries (Morocco, Algeria, Tunisia, Libya, Egypt, Jordan, Syria, Lebanon and Turkey) that helps them increase market access and develop trade policies which will facilitate the most efficient economic development. The study uses, the MacMap-HS6 database on market access and the Modeling International Relations under Applied General Equilibrium (MIRAGE) model of the global economy. While most South Mediterranean (SM) countries are very protectionist, they enjoy a fairly good access to world markets, either due to product specialization or to preferences granted by the European Union in the industrial sector. Today, these countries are simultaneously opting for multilateralism, North-South regionalism, and South-south regionalism. Are these options substitutes of each other? As this study suggests, that is not the case. A South-South integration of these countries is not enough trade – creating, while a North – South Free Trade Agreement with Europe is significantly trade – diverting, particularly in the case of SM countries’ agricultural imports. In order to examine the dynamics between multilateralism and regional strategies, the ‘structural congruence’ of these different trade regimes is measured and a new indicator is proposed.